KETUHANAN DAN KEMANUSIAAN YESUS KRISTUS BERDASARKAN INJIL YOHANES 1:1-18 - Laurens Tutupoly (Program Studi Pendidikan Agama Kristen, 2018)
This article is a description of the divinity and humanity of Jesus Christ. Based on the Gospel of John 1: 1- 18. The purpose of this paper is to show evidence of the divinity and humanity of Jesus Christ. The main points of discussion in this paper are the eternity of the Word / Christ; Unity of the Word and God; All things are made by the Word; Jesus Christ (the Word) is the Sustainer; The Word (Jesus Christ) is the Final Destination; Jesus Christ is the Giver of eternal life; The Word becomes man; Jesus incarnation for the work of salvation Abstrak: Artikel ini adalah sebuah deskripsi mengenai ketuhanan dan kemanusiaan Yesus Kristus. Didasarkan pada Injil Yohanes 1: 1- 18.Tujuan penulisan ini adalah untuk memperlihatkan bukti ketuhanan dan kemanusiaan Yesus Kristus. Adapun pokok-pokok pembahasan dalam penulisan ini adalah keabadian Firman/Kristus; Kesatuan Firman dan Allah; Segala Sesuatu dijadikan oleh Firman; Yesus Kristus (Firman) adalah Sang Pemelihara; Firman (Yesus Kristus) adalah Tujuan Akhir; Yesus Kristus adalah Pemberi hidup kekal; Firman menjadi manusia; Inkarnasi Yesus untuk karya keselamatan